EFEKTIVITAS KEMAMPUAN KERJA PEGAWAI KELURAHAN DALAM MEMBERIKAN PELAYANAN ADMINISTRASI KEPADA MASYARAKAT - Hidayat, Rachmat (PREDIKSI, 2016)
Kelurahan Bandara Kecamatan Sungai Pinang of services as a local device performing the duties which consist of four (4) fields consisting of Government Sector, Division of Development and Social Affairs. Public services are the focus of study disciplines of public administration in Indonesia, is still an issue that needs attention and comprehensive settlement in which the demands of public service as a sign of public discontent. Services is one of the cornerstones of the effort and a necessity of customers satisfaction that must be optimized either by individuals or organizations, because of the form of services provided is reflected in the quality of individuals or organizations that provide services. Technical analysis of the data by (Sanapiah Faisal (1999; 255-258) consists of three flow of activities, namely: 1) Reduction of data (data reduction) 2) Presentation of data (data display) 3) Draw conclusions. Manufacture / processing of Certificate / Administration is a document required by the society to take care of a variety of purposes, such as to offset the costs in hospitals, scholarships, card making and other residents. Service procedures in Kelurahan Bandara Kecamatan Sungai Pinang has a common procedure of existing services in other Urban Communities. The procedure in the service Certificate (manufacture KK, KTP, SKTM, Domicile, IMB and others) is needed by the community Kelurahan Bandara Kecamatan Sungai Pinang Kota Samarinda, among others: a) Simplicity of service at the level of village service River District Pinang Kota Samarinda can be said to be going well that the maintenance of the Certificate (KK manufacture, KTP, SKTM, Domicile, IMB and others). b) Clarity and certainty in the service is one thing that is very important for the community. c) assurance service time; Service delivery at the Urban Community office should be effective and efficient for people could be gaining the maximum service and satisfying. d) a fairness services ; The services provided to the public shall include all lifes and satisfaction in service. Conclusion with the quality of work discipline adequate government officials, the bureaucrats at the Urban Community is able to provide public services effectively. The process of public services tends to be determined by the level of discipline officers of serving the public interest. Discipline the good work will create a harmonious interaction, both among fellow officers with the bureaucrats or the officials with the public.